Study of Scleractinian Coral Recruitment in the Waters of Tanjung Pisok and Siladen Island, Bunaken National Park - Lenak, Maria Magdalena; Roeroe, Kakaskasen; Paruntu, Carolus; Mangindaan, Remy; Manembu, Indri; Rimper, Joice (Sam Ratulangi University, 2025)
The research aimed to determine the recruitment density value of scleractinian coral juveniles in Tanjung Pisok (Meras and Bahowo) and Siladen Island. The method for selecting observation locations uses purposive sampling and collecting coral juvenile recruitment data using underwater photo transects. The results of this research obtained data on genus, size, and density values ​​for coral juvenile recruitment. The coral genera found at Station I were 19 genera with the largest number being the Porites genus, 32 colonies, Station II 13 genera with the largest number being the Favites genus, 32 colonies, and at Station III 17 genera with the largest number being the Porites genus, 32 colonies. Coral juveniles in this study were more dominant in the 2 cm - 2.9 cm size group, for Station I 63 colonies, Station II 54 colonies and Station III 32 colonies. Based on the results of this research, it shows that the coral recruitment density at Station I with a value of 12.38 colonies/m² is higher than Station II, the coral recruitment density at Station II with a value of 12.23 colonies/m² is higher than Station III with a value of 7.21 colonies/m². Keywords: Recruitment; Scleractinia; Underwater Photo Transect; Bunaken National Park Abstrak Tujuan penelitian menentukan nilai densitas rekrutmen juvenil karang scleractinia di perairan Tanjung Pisok (Meras dan Bahowo) dan pulau Siladen. Metode pemilihan lokasi pengamatan menggunakan purposive sampling dan metode pengumpulan data rekrutmen juvenil karang menggunakan underwater photo transect. Hasil penelitian ini memperoleh data genus, ukuran dan nilai densitas rekrutmen juvenil karang. Genus karang yang didapat di Stasiun I yaitu 19 genus dengan yang terbanyak genus Porites 32 koloni, Stasiun II 13 genus dengan yang terbanyak genus Favites 32 koloni, dan Stasiun III 17 genus dengan yang terbanyak genus Porites 32 koloni. Juvenil karang dalam penelitian ini lebih dominan pada kelompok ukuran 2 cm - 2.9 cm, untuk Stasiun I 63 koloni, Stasiun II 54 koloni dan Stasiun III 32 koloni. Berdasarkan hasil penelitian ini menunjukkan densitas rekrutmen karang di Stasiun I dengan nilai 12,38 koloni/m² lebih tinggi dari Stasiun II, densitas rekrutmen karang di Stasiun II dengan nilai 12,23 koloni/m² lebih tinggi dari Stasiun III dengan nilai 7,21 koloni/m². Kata kunci: Rekrutmen; Scleractinia; Taman Nasional Bunaken; Underwater Photo Transect